The genus Omalus Panzer, 1801 (Hymenoptera, Chrysididae) from China, with descriptions of four new species - Wei, Na-sen (Pensoft Publishers, 2014)
Abstract. The Chinese species of the genus Omalus Panzer, 1801 are revised and keyed for the first time. Eight species are recorded, of which four are new to science and one is new to China: Omalus aeneus (Fabricius, 1787), Omalus berezovskii (Semenov-Tian-Shanskij, 1932), Omalus potanini (Semenov-Tian-Shanskij, 1932), Omalus imbecillus (Mocsáry, 1889) (new to China), Omalus helanshanus sp. n., Omalus probiaccinctus sp. n., Omalus pseudoimbecillus sp. n., and Omalus tibetanus sp. n.